Optimization of the Allocation of Material Resources in a Production Line: Workstation Load Balancing by Analogy with the Bin Packing Problem - Khabir, Abdelilah (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The obligation to use resources in an optimal way in production lines requires industrials to use the tools and methods of operational research and to mathematically model their resource allocation problems in order to find optimal configurations of their assembly lines. The objective of this paper is the implementation of a decision support tool to help manage and optimize the allocation of material resources of companies during the product launch phase. This tool must be able to be used at several levels: strategic and operational. The assembly lines balancing problem, which we study in this article, is distinguished by its configuration (constraint and hypothesis) related to the business environment studied, finally, for the resolution of the problem we made an analogy with the bin packing problem and then proposed a solution adapted to our case study.